The New Sakai: Efforts to construct the Sakai identity - Hijjang, Pawennari; El Amady, M Rawa; Hadi, Amnah (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
This study is about the transformation of the Sakai tribe regarding changes in the natural, socio-economic and political environment. The Sakai tribe has blended in with the community, owning companies, and holding political as well as government positions. Sakai now is the ‘new Sakai’ that is different from the ‘old Sakai’ stereotyped as backward, stupid, and introvert. The purpose of this paper is to describe the response of the Sakai tribe towards changes through their identity construction. We used ethnography as a method and the data was obtained by living in five kebatinan. The researcher lived at the research location, observed the situation, conducted in-depth interviews and had continuous discussions with the participant to deepen their understanding of the data. The data obtained was then then analyzed descriptively by discussing Warren's theory of identity construction and adaptation theory. This study found that the Sakai people adapt significantly to changes in the natural, socio-economic and political environment. One of the sources of this adaptability comes from education, that since the reformation, the Sakai people have massively made educational efforts for their younger generation. This study concludes that every community has the ability to adapt to changes in its environment based on the knowledge possessed by that community.